L’impact de la réaction policière sur l’évolution de vols avec violence - Élie, Daniel; Kapétanaki-Barake, Anne (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1985)
This descriptive and comparative study analyses the effectiveness of police activity on the evolution of robbery and armed robbery in four Canadian provinces and five metropolitan areas. The statistical data used were those furnished by Statistics Canada on cases of robbery, armed robbery, the clearance rate and the number of persons charged with these crimes. The evaluation of police effectiveness was made by analysing the variation in the rate of solution on the rate of crime and the rate of the number of persons accused on the rate of crime. The analysis showed that the influence of police action on the control of robbery and armed robbery, as expresses by the clearance rates is almost the same from one province or metropolitan area to another. Furthermore, the effectiveness of police action seems to depend on the volume of crime that the police have to cope with. Also, the analysis of the variation in the clearance rate and the rate of persons accused in relation to the rate of crime showed that an increase in the volume of crime is independent of the efforts made by the police.